Pendampingan Penyusunan Panduan Pembelajaran Teknologi Farmasi Berbasis Pjbl- Collaborative Teaching Untuk Inisiasi Produk Unggulan Farmasi Di Smk 2 Muhammadiyah Riau - Nurbaiti, Nurbaiti; Muhammad Arif; Neng Sholihat; Aldeva Ilhami (LPPM UMRI, 2026)
The Ministry of Education and Culture Regulation No. 22 of 2020 mandates the revitalization of Vocational High Schools (SMK) as centers of excellence to produce skilled workers that meet industry needs. The demands of 21st-century skills require students to possess critical thinking, creativity, and collaborative abilities. This community service program (PKM) aimed to improve the quality of pharmaceutical technology learning through the development of Project-Based Learning (PjBL) instructional materials. The program employed a participatory action research approach for its implementation, involving data collection through interviews, training sessions, practical demonstrations, observations, and questionnaires. The results indicate that teachers successfully developed valid and practical PjBL-based pharmaceutical teaching modules. Teachers’ skills in implementing PjBL were categorized as very good, as reflected in the high percentage of instructional implementation. The urgency of this community service focused on addressing partner challenges in developing PjBL-based learning materials, designing learning evaluations, and providing guidance for the implementation of PjBL through a lesson study approach.